Emotions and Literary Genres in the Testaments of the Twelve Patriarchs and the New Testament - Gemünden, Petra von 1957- (2016)
This essay argues that there is a relationship between the presentation and evaluation of emotions, on the one hand, and the genre(s) in which these are present, on the other hand. A significant difference can be observed between narrative and paraenetic texts. In narrative texts, we find a plurality of emotions that are evaluated in a differentiated manner, accepted as reality, and linked to the body. In paraenetic texts, emotions are often reduced to a single alternative. Great authorities urge one to avoid these emotions in future, whereas narratives tend to give the reader the opportunity to take one’s distance from them. Different anthropological possibilities of perceiving and coping with reality correspond to the different genres.
Keywords: emotion(s) -- genre -- Testaments of the Twelve Patriarchs -- New Testament -- envy -- anger -- desire